Reward reduces the fission illusion in the sound-induced flash illusion. (June 2022) - Yu, Gaoxin; Liu, Chunmei; Liu, Xiaole; Wang, Aijun; Zhang, Ming
Pairing a single visual stimulus with multiple auditory stimuli will lead to the illusory perception of multiple visual stimuli, which is known as sound-induced flash illusion (SIFI). The present study adopted the classic SIFI paradigm to investigate whether value-associated tasks could affect the SIFI. By adjusting the sequence of reward and nonreward conditions, we also examined the effect of reward history on SIFI. The results showed that the fission illusion was reduced when associated with momentary reward, demonstrating significantly higher accuracy and discriminability than the nonreward condition. However, the fusion illusion was not affected by the momentary reward, and the explanation was that the fusion illusion was not as stable as the fission illusion and disappeared across different trials and conditions. Moreover, the robustness of reward history in the present study was not as strong as previous studies have suggested, indicating that the effect of sound on the perceptual representation of visual stimuli is strong and robust to reward history. These findings demonstrated that the reward could reduce the SIFI and broaden the existing dichotomy of SIFI. New evidence for the operation of value-driven attention mechanisms is also provided, suggesting that the underlying value-driven attention operates across multiple sensory systems.